Palaeoseismology of Rocky Coasts - Evelpidou, N.; Pirazzoli, P. (Encyclopedia of Earthquake Engineering, 2015)
Important earthquakes are often accompanied by vertical-land displacements. Therefore in coastal areas they may result in rapid changes of the relative sea level. An essential tool for the study of coastal paleoseismicity is the identification of fossil paleoshorelines, paying special attention to sea-level indicators that are consistent or provide evidence of rapid relative sea-level change. Here, different types of sea-level indicators that are often used in literature in order to determine changes in fossil shorelines are summarized. Information is also provided regarding four case studies of important earthquakes that occurred in Greece (in AD 365, 1953, and 1956) and in Japan (in 1923).